Using nonconvergence of iteration to partition ODEs - Suleiman, Mohamed; Baok, Saiman (Elsevier, 1992)
Given is a variation of partitioning ODEs when using the multistep method. Essentially the nonconvergence property is made use of for partitioning. The criteria used are explained by using a test system of two linear equations and generalisation is made to a general system of first-order ODEs. Finally, some numerical results are given that include systems greater than two.